Optimasi Jumlah Hidroksipropil Metilselulosa dan Lama Pengadukan dalam Preparasi Hollow Microspheres Captopril - Eka Deddy Irawan; Firdatus Sholehah; Lidya Ameliana (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Captopril is an antihypertensive class of Angiotensin-Converting Enzyme Inhibitor (ACEI) used as one of the treatment of hypertension. Low bioavailability and short half-life of captopril caused side effects on gastrointestinal tract, thus it can be prepared into hollow microspheres. Hollow microspheres is spherical microparticles with 1-1000 µm hollow nucleus. Many factors influence the preparation of hollow microspheres including the amount of hydroxypropyl methylcellulose (HPMC) polymer and stirring time. In this study we investigated the best composition of the number of HPMC and stirring times which can produce captopril hollow microspheres with entrapment efficiency (EE), buoyancy, and optimum particle size. Hollow microspheres captopril was prepared using a non-aquoeous solvent evaporation method. The result was captopril hollow microspheres with 25 mg HPMC and 2 hours of stirring can produce an entrapment efficiency (EE) 97,796%, buoyancy 86,747% and particle size 205,655 µm. The yield hollow microspheres captopril 91.903% ± 2.547 with spherical shape, uneven surface morphology and hollow core. The results of FT-IR analysis showed that there was no interaction between the drug and the polymer used in the formulation.